Comprehensive and long‐term outcomes of enzyme replacement therapy followed by stem cell transplantation in children with Gaucher disease type 1 and 3. Issue 3 (23rd December 2022) - Anurathapan, Usanarat; Tim‐Aroon, Thipwimol; Zhang, Wujuan; Sanpote, Watinee; Wongrungsri, Siranee; Khunin, Nitcha; Chutipongtanate, Somchai; Chirdkiatgumchai, Vilawan; Ngiwsara, Lukana; Jaovisidha, Suphaneewan; Khongkraparn, Arthaporn; Pakakasama, Samart; et al.
Abstract: Background: Gaucher disease (GD) is a lysosomal storage disorder, characterized by hepatosplenomegaly, pancytopenia, bone diseases, with or without neurological symptoms. Plasma glucosylsphingosine (lyso‐Gb1), a highly sensitive and specific biomarker for GD, has been used for diagnosis and monitoring the response to treatment. Enzyme replacement therapy (ERT) is an effective treatment for the non‐neurologic symptoms of GD. Neuronopathic GD (type 2 and 3) accounts for 60%–70% of the Asian affected population. Methods: We explored combination therapy of ERT followed by hematopoietic stem cell transplantation (HSCT) and its long‐term outcomes in patients with GD type 3 (GD3). Results: Four patients with GD3 and one with GD type 1 (GD1) underwent HSCT. The types of donor were one matched‐related, one matched‐unrelated, and three haploidentical. The age at disease onset was 6–18 months and the age at HSCT was 3.8–15 years in the patients with GD3. The latest age at follow‐up was 8–22 years, with a post‐HSCT duration of 3–14 years. All patients had successful HSCT. Chronic graft‐versus‐host disease occurred in one patient. The enzyme activities were normalized at 2 weeks post HSCT. Lyso‐Gb1 concentrations became lower than the pathological value. All of the patients are still alive and physically independent. Most of them (4/5) returned to school. None of the patients with GD3 had seizures or additional neurological symptoms after HSCT, but showed varying degrees of cognitive impairment. Conclusions: ERT followed by HSCT could be considered as an alternative treatment for patients with GD3 who have a high risk of fatal neurological progression.